a Penggunaan Campuran Tepung Udang Rebon (Acetes Sp.) Dalam Pakan Komersil Terhadap Kecerahan Warna Ikan Komet (Carassius Auratus) - Viona Liuprilita Budiman; Ibnu Dwi Buwono; Kiki Haetami; Roffi Grandiosa (Jurnal Perikanan Unram, 2024)
This study aims to investigate the effect of adding shrimp head flour (Acetes sp.) to commercial feed on the color brightness of comet goldfish, as well as to determine the optimal usage level that can achieve the highest brightness level. The research method employed was a complete randomized design (CRD) with four treatments: (A) control 0%, (B) 10%, (C) 20%, and (D) 30% shrimp head flour. The study was conducted over 40 days, with observations made every 10 days using the Toca Color Finder to assess fish color. The results indicate that adding shrimp head flour to commercial feed significantly enhances the brightness of comet goldfish compared to the control, although there was no significant difference observed among treatments with varying levels of shrimp head flour. The highest increase in color brightness